Cybercrime Awareness Among Undergraduate Students : A Descriptive Study (International Journal of Scientific Research in Science and Technology, 2025)
Cybercrime has emerged as a critical global issue in the digital age, affecting individuals, institutions and governments. This study investigates the level of cybercrime awareness among undergraduate students (UG) in Arunachal Pradesh, India. Using a descriptive survey method, data were collected from a sample of 185 students across three colleges selected through simple random sampling. A standardized Cybercrime Awareness Scale developed by S. Rajasekar was used to assess awareness levels. Results revealed that while 10.81% of students demonstrated high awareness, a majority fell within moderate to low awareness categories, which is indicating a significant gap in digital safety knowledge. No statistically significant difference was observed between male and female students, and differences by academic stream were also not significant. These findings emphasize the urgent need to raise awareness and introduce cyber safety education into undergraduate curricula so that students can use digital platforms safely and responsibly.
Keywords: Cybercrime Awareness; UG Students; Digital Literacy; Cybersecurity Education